Elucidating the mechanisms of lipopolysaccharide-induced cognitive impairment in rats treated with tualang honey and its methanolic extraction - Yaacob, Wan Muhammad Hilmi Wan (2020)
Alzheimer’s disease (AD) is a neurodegenerative disease characterized by progressive loss of cognitive functions. The search for cognitive enhancers from natural products derivative has gained much attention. As a natural antioxidant source, Tualang honey (TH) produced by wild bees (Apis dorsata) is expected to have a positive influence on human health, including cognitive function. Four types of honey such as raw TH, irradiated TH, TH methanolic (MTH) and ethyl acetate extract were tested in the preliminary study and it was found that MTH exhibited the highest antioxidant potentials. Therefore, this study aimed to elucidate the mechanism of TH and MTH on lipopolysaccharide (LPS)-induced cognitive impairment in rats, and compare with memantine, one of the standard drugs used in the management of AD. A total of 100 male Sprague Dawley rats were randomly divided into 5 groups: (i) control, (ii) untreated LPS, (iii) LPS treated with 200 mg/kg TH, (iv) LPS treated with 150 mg/kg MTH and (v) LPS treated with 10 mg/kg memantine. All treatments were administered intraperitoneally once daily for 14 days. LPS was injected into the rats at Day 4 of the treatments to create neuroinflammatory responses that cause cognitive dysfunctions. Spatial and recognition memory functions were assessed using Morris water maze (MWM) and novel object recognition (NOR) tests. Twenty four hours after completing behavioural tests, all rats were sacrificed and hippocampal tissues were removed. Localization and expression of inflammatory markers in the hippocampal tissue were determined by immunohistochemistry analysis and Western blot. The levels of antioxidant enzymes, oxidative damage and amyloid deposition in rats’ hippocampal homogenates were determined by commercially available ELISA kits. Nissl staining of hippocampal slices was employed to determine neuronal count. The administration of LPS to rats resulted in spatial and recognition memory impairment. LPS also caused a significant increase in neuroinflammation as evidenced by the increase in COX-2, iNOS and TNF-α expression in hippocampal tissues. There was a marked reduction in the levels of antioxidant enzymes such as CAT, GPx, GR and SOD with the concomitant increase in MDA level and amyloid deposition following LPS administration. LPS also caused reduction in the number of Nissl positive neurons in all hippocampal regions. TH and MTH treatments for 14 days significantly improved spatial and recognition memory. Besides, TH and MTH were able to reduce neuroinflammation, oxidative stress, amyloid deposition as well as improve Nissl positive neuronal count in the hippocampus. The neuroprotective effects of TH and MTH were found to be comparable with memantine. In conclusion, this study showed that both TH and MTH could prevent LPS-induced spatial and recognition memory impairment via its anti-inflammatory, antioxidant and anti-amyloidogenic properties. Both TH and MTH have the potential to be used as alternative therapy to protect against memory decline in AD patients.